Strategi Branding Ambon Kota Kreatif Berbasis Musik (Ambon City of Music) - Latuheru, Rido; Laisila, Maya (Lembaga Layanan Pendidikan Tinggi Wilayah XII, 2022)
The existence of legal certainty is stipulated in the Ambon City Regional Regulation number 2 of 2019 concerning Ambon as a music-based creative city. This regulation was enacted on 20 June 2019 in Ambon. On October 31, 2019, Ambon was designated by UNESCO (United Nations Education, Scientific and Curtural Organization) as the City of Music. with the determination of Ambon city of music by UNESCO, the application of Ambon, a music-based creative city, should be held in accordance with the objectives of the Ambonese people. Music-based creative city as regulated by regional regulation number 2 of 2019. City Branding is a concept that developed from the term place branding. (Place Brand/Regional Identity). place branding is a new term which later stands for city branding. The purpose of this study was